Analisis Variasi Perbandingan Diameter Pulley terhadap Efisiensi pada Pembangkit Listrik Tenaga Mikro Hidro (Pltmh) dengan Turbin Archimedes Screw - Muhammad Lintang Saputra; Trisma Jaya Saputra; Rany Puspita Dewi (Pusat Riset dan Inovasi Nasional, 2024)
Renewable Energy Sources (NRE) must be used properly, as an effort to reduce the energy crisis and the impact of pollution. One of them is by developing Micro Hydro Power Plants (PLTMH). The type of turbine that has the potential to make PLTMH on rivers in Indonesia is a screw turbine. The purpose of this study is to find out the performance of PLTMH with a screw turbine using variations in pulley diameter ratios, namely 1:1, 3:2, 2:1, and 3:1. The results of this study show that the ratio of pulley diameter affects the performance of PLTMH in generating electrical power. The results obtained by the diameter ratio of 2:1 get maximum performance on each load on the generator with the generator power produced. The lowest results were obtained at a 1:1 diameter ratio variation on each load on the generator.